Impact of TB Stigma and Intervention Strategies: A Systematic Review - Meo, Christina Marina; Sari, Ni Ketut Putri Martha; Suhardin, Saverinus; Halimatunisa, Maulin (International Journal of Psychosocial Rehabilitation, 2020)
Tuberculosis (TB) is still a major public health problem worldwide. Stigmatization and replacement can prevent active TB patients from seeking medical care, overcoming their disease status, and can stop treatment. This study aims to review the impact and intervention strategies to reduce TB stigma. This assessment method is carried out by following the PRISMA guidelines. Search for articles was carried out in the empathy database (Pubmed, Scopus, Science Direct, Proquest) using relevant keywords. Initial findings identified 1,822 documents, with 19 remaining after applying the study criteria for 2015 to 2020, discussing the UK, journal articles discussing stigma in TB. Exclusion criteria are library priorities, discussion papers, comments, mini-reviews and stigma focused on HIV/AIDS patients. From 17 journals, 3 journals used mixed methods, 8 interview journals, and 6 cross-sectional journals. Reviews indicate the stigma of TB disease is still high, and is expressed through low self-esteem, humiliation, change, social exclusion and isolation, which cause a decrease in quality of life and delay in seeking health care/canceling a decrease in treatment. These findings illustrate that the majority of TB patients who correct the stigma associated with a number of factors that often hinder effective TB control. Therefore, intervention strategies that can be provided include health education, home visits, TB patient support, social support, financial support, and improving the quality of health workers.